Grouping of the enterprises based on the analysis of business-economic indices - Karachyna, N. P.; Kozachko, O. V.; Hrabko, M. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The efficiency of functioning of the milkprocessing enterprises of Vinnitsa region is analysed. The mathematical models of their grouping by the selected criteria are generated on the basis of production volume and profitability of their activity.